2017
DOI: 10.1111/cge.13059
|View full text |Cite
|
Sign up to set email alerts
|

A familial study of twins with severe asthenozoospermia identified a homozygous SPAG17 mutation by whole‐exome sequencing

Abstract: Asthenozoospermia (AZS) is a common cause of male infertility, characterized by abnormal reduction in the motility of ejaculated spermatozoa. Here, in a patient from a consanguineous family, we identified a homozygous mutation (c.G4343A, p.R1448Q) in SPAG17 by whole-exome sequencing. The encoded protein, SPAG17, localizes to the axonemal central apparatus and is considered essential for flagellar waveform. In silico analysis revealed that R1448Q is a potential pathogenic mutation. Immunostaining and western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…This can likely be attributed to nonsense‐mediated decay (NMD) resulting from the frameshift variant c.4127del, p.(Pro1376LeufsTer8). So far, a homozygous missense variant in SPAG17 c.4343G>A p.(Arg1448Gln) has been reported in one patient from a consanguineous family, putting forward SPAG17 as candidate gene for recessive male infertility (Figure S4; Xu et al, 2018). No second (likely) pathogenic SPAG17 variant could be identified however in F1 (III:2) by sequencing of all exons that had coverage below 20x in the WES data, by sequencing of the untranslated regions (UTRs) and by CNV analysis of all exons (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can likely be attributed to nonsense‐mediated decay (NMD) resulting from the frameshift variant c.4127del, p.(Pro1376LeufsTer8). So far, a homozygous missense variant in SPAG17 c.4343G>A p.(Arg1448Gln) has been reported in one patient from a consanguineous family, putting forward SPAG17 as candidate gene for recessive male infertility (Figure S4; Xu et al, 2018). No second (likely) pathogenic SPAG17 variant could be identified however in F1 (III:2) by sequencing of all exons that had coverage below 20x in the WES data, by sequencing of the untranslated regions (UTRs) and by CNV analysis of all exons (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A decreased expression of SPAG17 could be shown in fibroblasts of F1, II:8. No additional (likely) pathogenic variants could be found in the male infertility gene panel and so far only one homozygous missense variant has been reported in two twin brothers from a consanguineous family with severe asthenozoospermia (Xu et al, 2018). In parallel, homozygous variants in SPAG17 and WDR35 were described in a patient with multiple brain and skeletal anomalies, with a presumed combinatorial effect on the ciliary phenotype (Córdova‐Fletes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 23 eligible reports were used in the present systematic review, all of which were original articles. All genes discovered in these studies are listed in Table 1 [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] .…”
Section: Present Systematic Reviewmentioning
confidence: 99%
“…More recently, Wang et al [44] used whole exome-sequencing to identify an additional four consanguineous Chinese men with frameshift truncating mutations in DNAH1 , further establishing this gene’s role in flagellar development and motility during spermatogenesis. Further, Xu et al [45] identified homozygous mutations in two siblings of consanguineous parents with mutations affecting a highly conserved residue in sperm-associated antigen 17 ( SPAG17 ) causing asthenospermia. Functional studies showed this mutation causes significantly decreased SPAG17 expression in the patients’ spermatozoa, consistent with a functional role in motility [45] .…”
Section: Motility Anomalies (Asthenospermia and Flagellar Abnormalitimentioning
confidence: 99%
“…Recently, SPAG17 variants were reported to cause primary ciliary dyskinesia in human patients (Andjelkovic, Minic et al 2018). These variants are linked to male infertility due to severe asthenozoospermia (Xu, Sha et al 2018), and affect almost all stages of spermatogenesis in mice (Kazarian, Son et al 2018).…”
Section: Introductionmentioning
confidence: 99%